COLONIZING THE ‘COMMONS’ IN INDIA: IDEOLOGY, STATE AND INDIGENOUS PEOPLE (1860-1947) - Javeed Ul Aziz (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This paper delves into the historical intersection of ‘Commons’ and colonialism, examining how ideological paradigms during the colonial period shaped the regulation of locals' rights over these shared assets. Focusing on the experiences of pastoralists and forest dwellers, the study traverses through the evolution of colonial policies that sought to control and exploit the Commons for imperial gains. The analysis begins by unraveling the ideological frameworks underpinning colonization, exploring how European powers justified their control over the Commons through notions of progress, modernity, and civilization. The paper then traces the legal and administrative mechanisms implemented to regulate access and use of common resources, often at the expense of indigenous communities. Making use of a wide range of archival and oral history sources the paper attempts to assess the enduring impacts of these regulatory interventions on pastoralist and forest-dwelling communities in India generally and Kashmir in particular.